A Standardized Case Study Framework and Methodology to Identify "Best Practices” - Battisto, Dina; Franqui, Deborah (ARCC Conference Repository, 2014)
A review of the literature reveals limited information on how to conduct a facility-based case study yielding useful information for architectural practice. In the wake of an "evidence-based design ”movement, it is imperative for architects to think about case study research within a performance-based framework that links design decisions to measurable outcomes. Building on this premise, the objective of this paper is to argue for a standardized approach for case studies, present a framework and methodology providing guidance on how to conduct case studies, and conclude with an example. A six-step case study research process is presented including the purpose and activities for each step as well as possible deliverables. The authors claim that a standardized case study approach would allow for cross-case comparisons using a set of performance indicators. A desired end goal of case study research is to develop a facility database that could be used to inform the development of design guidelines, rules of thumb and "best practices.”